Some reflections about health communication in Spain after five years of the Observatory of Communication and Health - Terrón Blanco, J.L. (Revista Española de Comunicación en Salud, 2016)
This article aims to provide a series of reflections about communication and health in Spain. The text, merely descriptive and to some extent speculative, has been created from the direct experience that gives the direction of Centre for Communication and Health Studies InCom-UAB since 2005, the date of its founding and first entity that has dedicated his stable communication activity and health in our state. The article has two objectives: first, focusing on university research, a brief summary outline of what we have done and where we come from, and, secondly, to highlight our strengths and our weaknesses. But his ultimate purpose, without hiding some degree of provocation, is a necessary to promote theoretical dialogue about our areas of study: what is, what should be and what they are, whether to consider its goals.
Keywords: Health Communication; Spain; Perspectives